1. ROLES OF COMMUNITY ORGANIZATIONS IN RURAL DEVELOPMENT: Lessons Learned from Malaysia and Thailand - Muktasam Muktasam (JURNAL AGRIMANSION, 2004)
ABSTRACT Community Organizations (COs) have been seen as an intermediary institution through which rural development programs are promoted. Rural development programs use COs to facilitate social changes. In Indonesia for example, there are large number and many types of COs such as farmer groups, poverty groups, women groups, and saving groups. However, studies indicate that most COs ineffective and stagnant. This study was conducted to understand the roles of COs in promoting rural development in Malaysia and Thailand. Findings from this study indicate that the success of rural development in those countries has been due to strategic roles of COs. Lessons learned from this study highlighted that to promote better rural development, COs such as community groups could be an option, however, critical steps to establish and to run the COs should be considered seriously. ABSTRAK Organisasi masyarakat dipandang sebagai lembaga perantara dalam proses pembangunan pedesaan. Program-program pembangunan pedesaan menggunakan kelembagaan ini guna memfasilitasi proses perubahan sosial. Di Indonesia misalnya, dijumpai banyak jenis dan jumlah organisasi masyarakat seperti kelompok tani, kelompok masyarakat (pokmas dalam program IDT), dan kelompok wanita. Namun demikian, sejumlah studi menunjukkan banyak kelompok tidak efektif dan bahkan stagnan. Penelitian ini dilakukan untuk memahami peran organisasi masyarakat dalam pembangunan pedesaan di Malaysia dan Thailand. Temuan penelitian ini menunjukkan bahwa keberhasilan pembangunan pedesaan di kedua negara tersebut tidak terlepas dari peran strategis organisasi masyarakat. Pelajaran penting yang dipetik dari penelitian ini adalah bahwa organisasi masyarakat dapat menjadi pilihan dalam mencapai keberhasilan pembangunan pedesaan dengan catatan bahwa tahapan kritis dalam pembentukan dan pengelolaan organisasi masyarakat harus dipertimbangkan secara serius.